(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
In the article on the material of the famous Ukrainian writer novel about the consequences of the earthquake for a large Italian city deals with the problems of human existence in its tragic aspects. The author highlights key existential dimension of being represented in the product determines the characteristics of artistic realization. Attention is paid to the specific style of disclosure of psychological features of characters, the role and place of color portraits and symbolic details in the image of the human being.